Mycobacterial lipoarabinomannan negatively interferes with macrophage responses to Aspergillus fumigatus in-vitro - Luis E. Gonzales-Huerta; Thomas J. Williams; Renad Aljohani; Brian Robertson; Carlton A. Evans; Darius P. H. Armstrong-James (PLoS ONE, 2026)
Over 1 million people have chronic pulmonary aspergillosis (CPA) secondary to pulmonary tuberculosis. Additionally, Aspergillus fumigatus ( Af ) has been reported as one of the most common pathogens associated with mycobacteria in patients with cystic fibrosis. Mycobacterial virulence factors, like lipoarabinomannan, have been shown to interfere with host’s intracellular pathways required for an effective immune response, however, the immunological basis for mycobacterial-fungal coinfection is still unknown. We therefore investigated the effect of lipoarabinomannan on macrophage responses against Af . Bone marrow-derived macrophages (BMDMs) were stimulated with non-mannose-capped lipoarabinomannan (LAM) from Mycobacterium smegmatis or mannose-capped lipoarabinomannan (ManLAM) from Mycobacterium tuberculosis for 2 hours and then infected with swollen Af conidia. Cell death was assessed by lactate dehydrogenase release. Cytokine release was measured in supernatant using Enzyme Linked Immuno-Sorbent Assay (ELISA). Colony forming units counting and time-lapse fluorescence microscopy was performed for studying conidia killing by macrophages. BMDMs stimulated with LAM showed increased cell death and inflammatory cytokine release in a dose-dependent manner, characterised by a significant increase of IL-1β release. Time-lapse fluorescence microscopy and CFUs revealed that both LAM and ManLAM significantly decrease the capacity of macrophages to kill Af conidia within the first 6 hours of infection. The mycobacterial virulence factor, lipoarabinomannan, disrupts macrophage capacity to efficiently clear Af at early stages of infection in-vitro .